2021
DOI: 10.3390/children8030189
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Septic Arthritis of the Knee Due to a Multi-Sensitive Streptococcus pyogenes Strain Responsive to Clindamycin—A Case Report

Abstract: Septic arthritis is an inflammatory process usually generated by a bacterial infection. The knee is one of the most frequently involved joints. The etiology varies depending on age, and hematogenous spread remains the primary cause in children. Herein, we report a case of a previously healthy three-year-old female who was referred to our institution for acute swelling of her right knee. After a clinical and radiological diagnosis of septic arthritis, an empirical treatment with a combination of cefotaxime and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…There are drawbacks to MRI, which are expensive and require sedation or general anesthesia in the neonate. 14 In this patient, genu X-Ray and USG of genu have been performed, giving well visualization. Although good visualization, MRI is still needed to know the lesion of bone further and the bone infection spread.…”
Section: Case Reportmentioning
confidence: 89%
See 1 more Smart Citation
“…There are drawbacks to MRI, which are expensive and require sedation or general anesthesia in the neonate. 14 In this patient, genu X-Ray and USG of genu have been performed, giving well visualization. Although good visualization, MRI is still needed to know the lesion of bone further and the bone infection spread.…”
Section: Case Reportmentioning
confidence: 89%
“…Additional antibiotics should be considered in children not immunized against Hib. 14 Some infection societies and specialists have recommended 4 to 6 weeks of antibiotics by intravenous. 11 However, most studies pertain to osteomyelitis and septic arthritis in neonates have reported shorter intravenous regimens (from approximately 1-4 weeks).…”
Section: Case Report Commonest Bacteria Found In the Infectionmentioning
confidence: 99%